One way to find the value of 6t is to find the value of one t and then multiply it by 6.
Finding the value of 1 t
3t - 7 = 5t
1) Subtract 3t from both sides to get all the t terms on the same side
After you subtract, you get this:
- 7 = 2t
2) Divide both sides by 2 to isolate t
Dividing both sides by 2 gives you this:
- 7/2 = t
~~~~~~~~~~~~~~~~~~~~~~~~~~
If one t is worth - 7/2, then
5t = 5 ( -7/2)
5t = - 35/2
Also, if 1t = - 7/2, then
6t = 6 ( -7/2)
6t = - 42/2 <-- answer
Reduced to lowest terms
6t = - 21 <-- same answer
~~~~~~~~~~~
If you just subtract 3t from both sides of the original equation, you will quickly get an answer for "2t"
3t - 7 = 5t
1) Subtract 3t from both sides
- 7 = 2t
Once you know how much "2t" is, you can find "6t" by multiplying by 3
2t = - 7
3(2t) = 3 (- 7)
6t = - 21 <-- same answer
~~~~~~~~~~~~~~~~~~
Answer:
If 5t = 3t - 4 <-- given in the problem
Then
1t = - 7/2
2t = - 7
6t = - 42/2 = - 21 <-- answer
~~~~~~~~~~
Note: 3 minus 7 doesn't really give 4.
3 - 7 gives MINUS 4
3 - 7 = - 4
7 - 3 = 4